2015
DOI: 10.1159/000370195
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Lectin-Like Oxidized Low-Density Lipoprotein Receptor 1 Protects against Plasma/Hypoxia-Mediated Trophoblast Dysfunction Associated with Preeclampsia

Abstract: Background: Preeclampsia (PE) is associated with oxidative stress in the maternal circulation and placenta. This study aimed to determine if inhibition of lectin-like oxidized low-density lipoprotein receptor 1 (LOX-1) gives protection against oxidative stress-mediated trophoblast dysfunction. Methods: Plasma and placenta samples were obtained from 106 women with PE and 106 women with normal pregnancy (NP). Oxidized low-density lipoprotein (oxLDL) and soluble LOX-1 levels were determined by enzyme-linked immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…However, they found that methylglyoxal, which is involved in vascular complications of diabetes mellitus and the development of hypertension, is a possible factor that affects LOX-1 and arginase because it is able to induce oxidative stress in vascular cells. Another finding by Zhang and colleagues suggests that LOX-1 accumulation may contribute to the development of PE by promoting sFlt-1 production in trophoblasts ( 23 ). This group was able to inhibit LOX-1 and protect against oxidative stress-mediated trophoblast dysfunction.…”
Section: Endothelial Dysfunction Pregnancy and Innate Immunitymentioning
confidence: 99%
“…However, they found that methylglyoxal, which is involved in vascular complications of diabetes mellitus and the development of hypertension, is a possible factor that affects LOX-1 and arginase because it is able to induce oxidative stress in vascular cells. Another finding by Zhang and colleagues suggests that LOX-1 accumulation may contribute to the development of PE by promoting sFlt-1 production in trophoblasts ( 23 ). This group was able to inhibit LOX-1 and protect against oxidative stress-mediated trophoblast dysfunction.…”
Section: Endothelial Dysfunction Pregnancy and Innate Immunitymentioning
confidence: 99%
“…The role of oxidative stress in the pathophysiology of PE has increasingly been postulated thus: reactive oxygen species produced by the relatively hypoxic placenta is transferred to the maternal circulation and it subsequently causes endothelial dysfunction [10]. Moreover oxidative stress may be an important mediator regulating angiogenic pathways in trophoblasts [11]. The pathogenesis of PE involves a number of biological processes that may be directly or indirectly affected by vitamin D, including immune dysfunction, placental implantation, pregestational insulin resistance, abnormal angiogenesis, excessive inflammation, and hypertension [12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Although the physiopathology associated with preeclampsia (PE) is unclear, oxidative stress appears to be an important contributing factor [1]. Heme oxygenase-1 (HO-1) is an inducible enzyme that catalyzes heme degradation, which triggers the synthesis of iron, biliverdin, and carbon monoxide, resulting in anti-inflammatory and anti-apoptotic effects, and oxidation resistance [2,3].…”
Section: Introductionmentioning
confidence: 99%